How do you multiply (4n23n+7)(8n25n2)?

2 Answers
May 4, 2018

32n4+44n333n229n14

Explanation:

Multiply all three terms in the second bracket by each of the three terms in the first bracket.

(4n23n+7)(8n25n2)=

32n4+20n3+8n2+24n3+15n2+6n56n235n14

Now collect like terms

32n4+44n333n229n14

May 4, 2018

=32n4+44n333n229n14

Explanation:

Step by step, multiply out the first term separately with each term in the second pair of brackets. Then take the second term in the first bracket and multiply out with each term in the second pair of brackets. Complete by doing the third term in the first bracket multiplied by each term of the second bracket. Complete by simplification:

(4n23n+7)(8n25n2):

(4n2)(8n2)=32n4

(4n2)(5n)=20n3

(4n2)(2)=8n2

Proceed to take second term of first bracket and multiply by each term in the second bracket:

(3n)(8n2)=24n3

(3n)(5n)=15n2

(3n)(2)=6n

Then take the last term in the first pair of brackets and multiply out with each term in the second pair of brackets:

(7)(8n2)=56n2

(7)(5n)=35n

(7)(2)=14

Now write all terms that have been expanded together:

=32n4+20n3+8n2+24n3+15n2+6n56n235n14

Simplify:

=32n4+44n333n229n14